QUARTERLY SCORES LIST. (Notes, 2026)
The article provides a detailed list of new music publications compiled for potential review, aimed at assisting libraries and individuals in selecting and ordering music editions. It categorizes the publications into various genres, including scholarly and historical editions, orchestral music, band music, choral music, and chamber music, among others. Each entry includes essential details such as the title, editor, publisher, ISBN, and pricing, facilitating easy reference for those interested in acquiring new music materials. The article also outlines the citation style used for the listings, ensuring clarity and consistency in referencing the publications.